2020
DOI: 10.4018/978-1-7998-0311-9.ch011
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Dyes From Wastewater by Adsorption Onto Low-Cost Adsorbents

Abstract: This chapter describes an up-to-date critique of the use of adsorption as a wastewater treatment technique for the removal of dyes. The topics range from the classification of dyes, their occurrence in water and toxicity, various treatment methods, and dye adsorption dynamics onto agricultural wastes and inorganic adsorbents such as clay and metal oxides and adsorption onto microbial biomass under varying operational conditions. It is demonstrated that the discussed materials form alternative adsorbents for dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Among the dye sequestration techniques, adsorption onto activated carbon remains the widely used method for discoloration of aqueous solutions (Markovska et al 2001). However, activated carbon is not only expensive, but also demanding to regenerate, necessitating the search for alternative low-cost, naturally available and sustainable adsorbents such as clays (Li et al 2010;Shikuku et al 2019). Karim et al (2017) reported effective removal of Basic Red 46 (BR46), methylene blue (MB) and malachite green (GM) cationic dyes onto a Moroccan clay.…”
Section: Introductionmentioning
confidence: 99%
“…Among the dye sequestration techniques, adsorption onto activated carbon remains the widely used method for discoloration of aqueous solutions (Markovska et al 2001). However, activated carbon is not only expensive, but also demanding to regenerate, necessitating the search for alternative low-cost, naturally available and sustainable adsorbents such as clays (Li et al 2010;Shikuku et al 2019). Karim et al (2017) reported effective removal of Basic Red 46 (BR46), methylene blue (MB) and malachite green (GM) cationic dyes onto a Moroccan clay.…”
Section: Introductionmentioning
confidence: 99%
“…Relatively recently, certain forms of waste have begun to be used as adsorbent material to remove various dyes from waters and have been found to be very effective in removing indigo carmine from the aquatic environment. The most used wastes for water decontamination are sunflower stalks, corn cobs, sugarcane stalks, rice husks, wheat husks, clay, and paper [ 67 , 90 , 91 , 92 , 93 ].…”
Section: Indigo Carmine In the Textile Industrymentioning
confidence: 99%